Advances in Micropropagation of Commercial Pecan Cultivars. (14th September 2020) - Vahdati, Kourosh; AjamGard, Fereidoon; Rahemi, Majid; Driver, John
ABSTRACT: Pecan, [ Carya illinoinensis (Wangenheim) C. Koch] is a nut crop of growing worldwide interest and importance. In this research, a micropropagation protocol was developed during 2015–2016 using five pecan cultivars ('GraTex', 'Wichita', 'Choctaw', '10 J' and 'GraKing'). In the establishment phase, nodal segments of mature pecan trees were collected 9, 13, 17, 21, and 25 days after bud-break and maintained at 4°C for 0, 24, 48, or 72 hours. Next, they were soaked in 2.5% sodium hypochlorite for 1, 2, 3, 4, 5, 6, or 7 minutes. Each explant was cultured on DKW medium individually. For proliferation phase, the best established shoots were cut into nodal segments and cultured on DKW medium supplemented with different BA concentrations (4.44, 13.30, 22.20, and 44.40 µM). Proliferating cultures were established and microshoots were rooted on MS medium containing IBA (4.9, 14.7, 24.5, and 49.0 µM) for 6 days in the dark. Date of cutting field-grown shoots for explanting had a significant effect on disinfection and culture establishment, with optimum success 11–15 days after bud break. Preliminary chilling treatment (4°C for 48 h) prior to cutting into nodal segments improved explant establishment. The best proliferation rate was obtained using 22.2 µM BA. Root induction using 24.5 µM IBA gave the highest rooting percentage. Rooted microshoots were successfully transferred to pots. Although the 'Wichita' and '10 J' cultivars had the highest success for acclimatization (89% and 84% respectively) the difference between cultivars was not significant and plantlets of five pecan cultivars were successfully acclimated. The results of this research can be applied by the authors in commercial level.